2013
DOI: 10.1063/1.4825264
|View full text |Cite
|
Sign up to set email alerts
|

Gold shunt pads as a chirality filter for current-driven 360° domain wall motion in a ferromagnetic wire

Abstract: Articles you may be interested inFaster motion of double 360° domain walls system induced by spin-polarized current

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Moreover, instead of Walker Breakdown as observed in 180DWs, a 360DW is predicted to undergo annihilation at a sufficiently high spin current density. Simulations predict that 360DWs of different chirality can be filtered [16], and 360DWs have been proposed for use in magnetic sensors [17] and as an alternative to 180DWs in memory and logic.…”
mentioning
confidence: 99%
“…Moreover, instead of Walker Breakdown as observed in 180DWs, a 360DW is predicted to undergo annihilation at a sufficiently high spin current density. Simulations predict that 360DWs of different chirality can be filtered [16], and 360DWs have been proposed for use in magnetic sensors [17] and as an alternative to 180DWs in memory and logic.…”
mentioning
confidence: 99%
“…[34,35]. Within the steady motion regime, we found that the DW velocity is V DW (t) = u(t) × β α for the NWs, where u is the spin current velocity inside the nanowire [11].…”
Section: (A) and (B) With Three Regions Of Dw Structurementioning
confidence: 88%
“…Nearby 180DWs in a wire can interact via their stray fields, annihilating spontaneously or forming a 360° domain wall (360DW), depending on their type (VW or TW), their relative chirality and the geometry of the wire [10]. 360DWs have distinct behaviors compared to 180DWs under the influence of current and magnetic field [11][12][13][14][15][16][17] and their formation is therefore important in DW devices in which the walls are close enough to interact, playing a key role in device performance, including speed, capacity and reliability.…”
mentioning
confidence: 99%
“…Ferromagnetic domain walls (DWs) in thin film wires can be translated by an electric current using spin torque transfer effects [Berger 1978, Tatara 2004, Thiaville 2007, Beach 2008, Zhang 2013] making them promising for applications in memory [Parkin 2008] and logic [Currivan 2012, Allwood 2005] devices, and spurring intense interest in their structure and behavior. In a thin film wire made from a low anisotropy ferromagnet such as Permalloy (Ni 80 Fe 20 ), the domain wall can adopt a transverse wall (TW) or vortex wall (VW) configuration depending on the wire width and thickness, according to both simulations and experimental observations [McMichael 1997, Kläui 2004].…”
Section: Introductionmentioning
confidence: 99%